Предмет: Алгебра,
автор: bekturjoldoshbekov5
помогите пожалуйста срочно
Приложения:
Ответы
Автор ответа:
0
Ответ: -15.
Объяснение:
∫₋₂¹(6x²+2x-10)dx = ∫₋₂¹(6x²)dx + ∫₋₂¹(2x)dx -∫₋₂¹(10)dx =
= 6∫₋₂¹(x²)dx +2∫₋₂¹(x)dx - 10∫₋₂¹(1)dx = 6/3(x³)|₋₂¹ + 2/2(x²)|₋₂¹-10(x)|₋₂¹ =
= 2(1³-(-2)³)+(1²-(-2)²)-10(1-(-2)) = 2*9 +(-3) -30 = 18-3-30 = -15.
Похожие вопросы
Предмет: Химия,
автор: romchikkostiuk
Предмет: Другие предметы,
автор: Аноним
Предмет: Геометрия,
автор: wainbaum
Предмет: Литература,
автор: butakov2608
Предмет: Математика,
автор: tanaborisuk92